Multi-parametric Point of Care Device for Allergen-specific IgE Detection in Veterinary Applications. (2016) - Elizalde, J.; Mayora, K.; Rivas, L.A.; Sanz, A.J.; Tolentino-Cortez, T.; Barreda-Gómez, G.; Tijero, M.
Abstract: This paper reports the first validation results of a promising point of care device based on an injected plastic microfluidic cartridge and commercial off the shelf components. An 8x8 spotted array is immobilized in the incubation chamber inside the cartridge, and once the chemical reactions have been finished, the colorimetric results are captured by a CMOS camera. The captured image of the array is analysed in terms of intensity levels at each spot location. This device is intended to detect allergen specific IgE in veterinary applications, but it can also be applied to any application based on ELISA like protocols.